Prevalence and determinants of healthy and balanced diet among office workers in a sedentary working environment: evidence from Southern Sri Lanka - Janaka Godevithana; Champa Jayalakshmie Wijesinghe; Millawage Supun Dilara Wijesinghe (BMC Public Health)
Abstract Background An unhealthy diet is a key risk factor for non-communicable diseases (NCD), which account for a significant number of premature deaths and disability-adjusted life years worldwide. Office workers are reported to have unhealthy and unbalanced diets, while being sedentary due to the nature of their work, placing them at a greater risk of NCD. This study aimed to determine dietary intake and associated factors among sedentary office workers in Southern Sri Lanka. Methods A cross-sectional study was conducted among 518 sedentary workers in 20 offices in the Galle district. Socio-demographic, health and work-related factors and dietary practices were assessed using a self-administered questionnaire. Twenty-four-hour dietary recall was used to assess dietary intake, which was converted into the number of servings from each food group. Healthy dietary intake was defined as ‘adherence to the numbers of servings recommended in Food Based Dietary Guidelines for Sri Lankans for more than three food groups including cereal and cereal-based foods, fruits, and vegetables, with the consumption of one or no unhealthy food per day’. Results Only 4.6% (n = 24) of the participants consumed a healthy diet, while a considerable proportion had the recommended intake of cereal-based foods, vegetables and fish, meat and pulses (65.3%, 65.8% and 50.8%, respectively). Intake of fruits, dairy products, nuts and seeds was low among the participants. Meal skipping and group eating were significantly associated with an overall unhealthy diet. Stratified analysis showed sex as an effect modifier for the association between group eating and unhealthy diet. In multivariate analysis, none of the factors showed a significant association with healthy dietary intake. Conclusions The dietary intake of sedentary office workers was not up to the recommendations. Meal skipping and group eating were associated with unhealthy dietary intake. This study recommends introducing interventions to improve the intake of fruits, dairy products, nuts, and seeds for sedentary office workers.